PEMBERDAYAAN MASYARAKAT USAHA MIKRO KECIL MENENGAH (UMKM) DALAM PELATIHAN PEMBUATAN KUE KERING - Ajizah, Ratna Utami Nur; Jauhari, Irfan (Institut Agama Islam Riyadlotul Mujahidin, 2022)
Community empowerment activities are a conscious and planned effort carried out by the community which aims to make the community empowered, from those who cannot become able, from those who are unable to become capable by utilizing the potential that exists in the community environment. This community empowerment activity in the economic sector is carried out because it is based on problem identification, namely the low income of the community due to limited access to business, the community still does not have sufficient knowledge or skills to help improve the economy or increase family income through UMKM. This article aims to describe efforts to empower the community in the economic sector through Cookies UMKM in Dayakan Village, Badegan Ponorogo.